Pengaruh Luas Lahan Dan Pengalaman Berusahatani Terhadap Pendapatan Petani Padi Di Desa Taraitak I Kecamatan Langowan Utara Kabupaten Minahasa - Tunas, Olivia Octavia; Ngangi, Charles Reijnaldo; Timban, Jean Fanny Junita (AGRI-SOSIOEKONOMI, 2023)
This study aims to analyze the effect of land area and farming experience on the income of rice farmers in Taraitak I Village, North Langowan District, Minahasa Regency. This research was conducted for 3 months located in Taraitak 1 Village, North District, Minahasa Regency. The data analysis method used in this research is quantitative. The data used are primary data and secondary data. Primary data were obtained through interviews using a questionnaire (questionnaire) to rice farmers in Taraitak Satu Village, North Langowan District. Secondary data were obtained from the Village Office and various agencies involved in this study with various literature available in libraries and the internet. The results showed that the income of lowland rice farming in Taraitak 1 Village, North Langowan District was IDR4,258,814 per planting season with partial influence (t test) of the land area, the result of t count was 4,206 with a probability of 0,000 where this was stated there is a positive and significant effect on rice farming income and from farming experience obtained t count of 0.064 with a probability of 0.950 where it is stated that there is no positive and significant effect on farming income While for simultaneous effects (Test F) results obtained t count of 8,847 with a probability of 0,001 where it is stated that there is a positive and significant effect on farming income.